Reduced global functional connectivity of the medial prefrontal cortex in major depressive disorder - Murrough, James W. (Hum Brain Mapp, 2016)
Background Major depressive disorder is a disabling neuropsychiatric condition that is associated with disrupted functional connectivity across brain networks. The precise nature of altered connectivity, however, remains incompletely understood. The current study was designed to examine the coherence of large‐scale connectivity in depression using a recently developed technique termed global brain connectivity. Methods: A total of 82 subjects, including medication‐free patients with major depression (n = 57) and healthy volunteers (n = 25) underwent functional magnetic resonance imaging with resting data acquisition for functional connectivity analysis. Global brain connectivity was computed as the mean of each voxel's time series correlation with every other voxel and compared between study groups. Relationships between global connectivity and depressive symptom severity measured using the Montgomery‐Åsberg Depression Rating Scale were examined by means of linear correlation. Results: Relative to the healthy group, patients with depression evidenced reduced global connectivity bilaterally within multiple regions of medial and lateral prefrontal cortex. The largest between‐group difference was observed within the right subgenual anterior cingulate cortex, extending into ventromedial prefrontal cortex bilaterally (Hedges' g = −1.48, P < 0.000001). Within the depressed group, patients with the lowest connectivity evidenced the highest symptom severity within ventromedial prefrontal cortex (r = −0.47, P = 0.0005). Conclusions: Patients with major depressive evidenced abnormal large‐scale functional coherence in the brain that was centered within the subgenual cingulate cortex, and medial prefrontal cortex more broadly. These data extend prior studies of connectivity in depression and demonstrate that functional disconnection of the medial prefrontal cortex is a key pathological feature of the disorder. Hum Brain Mapp 37:3214–3223, 2016. © 2016 Wiley Periodicals, Inc.